Comparing Perceptions of Oral Corrective Feedback Between Beginner and Intermediate Level EFL Undergraduate Students - Graciela Ferreiro (FOSTER: Journal of English Language Teaching, 2024)
This study investigated the preferences of adult English as a Foreign Language (EFL) learners regarding Oral Corrective Feedback (OCF), an essential component of language teaching and learning. The research addressed a gap in the existing literature by conducting a cross-sectional, mixed-methods study with a sample of 21 intermediate-level university students in Costa Rica. The study aimed to determine the participants' overall perception of OCF, the types of errors they considered worthy of correction, and their preferences for different modes of oral correction. The findings were then compared to the results of a previous study conducted by the researcher in 2023 with beginner-level EFL learners. Statistical analysis revealed that, like their beginner counterparts, the intermediate-level students have a significantly positive perception of OCF in language development. Both cohorts appreciated correcting all types of errors, with intermediate students placing slightly more emphasis on pronunciation-related errors. In both groups, the preferred feedback type was an explicit correction, while the least preferred was no correction, metalinguistic indication, and non-verbal cues. These findings contribute to the limited research on adult EFL learners' preferences for OCF in Latin American contexts, providing valuable insights for language instructors and researchers.